Villa Rica del Espiritu Santo : estudo histórico de uma cidade espanhola no Paraná (1570-1632) - Cardoso, Suelen Andrade (2015)
The aim of this work is to develop a historical study of the ancient Spanish city, Vila Rica of the Holy Spirit, located in the region comprising the current city of Phoenix / Pr. Villa Rica was founded in the late sixteenth century by Captain Ruy Diaz Melgarejo, in the area between the Ivaí and Piquiri rivers, believing that there were no gold mines. Villa Rica was the third community founded by the Spaniards in the then Province Del Guaira. In the year 1589, there was the transfer of Villa Rica on the orders of Captain Guzman to close the mouth Corumbataí in Ivaí. However, this change did not please the townspeople, because in this place the inhabitants of the first foundation had more natural resources and more Indians who worked under the encomienda system. In 1632, with the São Paulo flag, there was the siege of Villa Rica and its destruction. The purpose of this historical research was rebuild by consulting on primary sources and historiography the rationale behind the founding of Villa Rica as defense strategy guairenho territory